2010
DOI: 10.1177/0022034510365662
|View full text |Cite
|
Sign up to set email alerts
|

Altered Enamelin Phosphorylation Site Causes Amelogenesis Imperfecta

Abstract: Defects in the enamelin gene (ENAM) cause amelogenesis imperfecta (AI). Our objective was to identify the genetic etiology of enamel hypoplasia in a Caucasian proband. Our hypothesis was that ENAM was defective. The proband and his father have an AG insertion (g.13185_13186insAG; p.422FsX448) in ENAM previously identified in AI kindreds from Slovenia and Turkey. The proband, his brother, and his mother have a novel missense mutation (g.12573C>T) that substitutes leucine for a phosphorylated serine (p.S216L) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 37 publications
2
52
0
1
Order By: Relevance
“…The original identification of Fam20C solved the long-standing conundrum of which kinase is responsible for phosphorylating the milk protein casein, along with other secreted phosphoproteins involved in bone and teeth formation (14). Lethal mutations in Fam20C in humans result in the development of Raine syndrome, a neonatal osteosclerotic bone dysplasia that frequently involves ectopic calcification (12,23), whereas nonlethal mutations have been linked to hypophosphatemic rickets and amelogenesis imperfecta, a developmental tooth disease (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original identification of Fam20C solved the long-standing conundrum of which kinase is responsible for phosphorylating the milk protein casein, along with other secreted phosphoproteins involved in bone and teeth formation (14). Lethal mutations in Fam20C in humans result in the development of Raine syndrome, a neonatal osteosclerotic bone dysplasia that frequently involves ectopic calcification (12,23), whereas nonlethal mutations have been linked to hypophosphatemic rickets and amelogenesis imperfecta, a developmental tooth disease (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Fam20C phosphorylation of FGF23 impacts the cellular processing of FGF23, and loss of Fam20C activity results in hypophosphatemic rickets (18,25). In addition, the Ser216Leu mutation in enamelin results in amelogenesis imperfecta (24,26); in this case, the Ser is mutated within the S-x-E motif, blocking Fam20C phosphorylation, similar to S96A-HRC. Another example is a missense mutation of Ser91 in BMP4 that leads to renal hypodysplasia (13,27).…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed literatures regarding AI clinical phenotypes, enamel ultrastructure and the disease-causing gene mutations, and tried to establish the correlation among them (see Table II) 2,18,[20][21][22][23][24][25][26][27][28][29][30][31][32] . From the literatures review and our study, no specific correlation among the clinical phenotypes, ultrastructure and gene mutations was found for AI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Various mutations in the AMELX gene, encoding the most abundant extracellular matrix protein amelogenin in developing enamel [Du et al, 2005], have been well demonstrated to be causative for the X-linked forms of AI with a variety of phenotypes ranging from smooth hypoplastic to hypomaturation AI [Wright, 2006]. The autosomal dominant hypoplastic AI is associated with mutations in the ENAM gene, in which several mutations cause dosage-dependent phenotype with generalized hypoplastic AI segregating as a recessive trait [Ozdemir et al, 2005;Wright, 2006;Chan et al, 2010]. The enamelin protein is an enamel-specific protein secreted by ameloblasts in relatively low amounts (1-5% of matrix).…”
mentioning
confidence: 99%